2021
DOI: 10.1039/d1ra03744g
|View full text |Cite
|
Sign up to set email alerts
|

Cationic polymer-grafted graphene oxide/CNT cathode-coating material for lithium–sulfur batteries

Abstract: A cathode-coating material composed of cationic polymer-grafted graphene oxide (CPGO) and carbon nanotube (CNT) was prepared and used as a cathode-coating material for lithium sulfur batteries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 70 publications
(92 reference statements)
0
1
0
Order By: Relevance
“…At the same time, under the condition of low electrolyte dosage, the infiltration ability of electrolytes to electrode material and the migration ability of lithium ions in the cathode under the high content of active substances are particularly important . The former requires the binder of the cathode to have good wetting performance, which enables good contact between the active materials and the electrolyte, leading to the rapid gain and loss of electrons. , However, low electrolyte dosage largely increases the concentration of polysulfides in the electrolyte during the electrochemical reaction process and consequently results in the high viscosity of the electrolyte, which hinders the ion transfer in the electrolyte and eventually obstructs the further occurrence of reversible electrochemical reactions. , An effective way to decrease the concentration of in situ formed polysulfides in the electrolyte is electrostatic adsorption of the polysulfides onto the cathode. To create positively charged adsorption sites in the cathode, cationic polymers are commonly adopted as the binder. However, no studies have demonstrated the feasibility of using cationic binders to construct lean electrolyte Li–S batteries with high sulfur loading mass as the previously reported cationic binders fail to provide high ion conductivity.…”
mentioning
confidence: 99%
“…At the same time, under the condition of low electrolyte dosage, the infiltration ability of electrolytes to electrode material and the migration ability of lithium ions in the cathode under the high content of active substances are particularly important . The former requires the binder of the cathode to have good wetting performance, which enables good contact between the active materials and the electrolyte, leading to the rapid gain and loss of electrons. , However, low electrolyte dosage largely increases the concentration of polysulfides in the electrolyte during the electrochemical reaction process and consequently results in the high viscosity of the electrolyte, which hinders the ion transfer in the electrolyte and eventually obstructs the further occurrence of reversible electrochemical reactions. , An effective way to decrease the concentration of in situ formed polysulfides in the electrolyte is electrostatic adsorption of the polysulfides onto the cathode. To create positively charged adsorption sites in the cathode, cationic polymers are commonly adopted as the binder. However, no studies have demonstrated the feasibility of using cationic binders to construct lean electrolyte Li–S batteries with high sulfur loading mass as the previously reported cationic binders fail to provide high ion conductivity.…”
mentioning
confidence: 99%